Benefits of hormone treatment of both sexes in semi-artificial reproduction of pikeperch (Sander lucioperca L.) - M. Blecha; A.M. Samarin; J. Křišťan; T. Policar (Czech Journal of Animal Science, 2016)
Propagation of pikeperch Sander lucioperca by semi-artificial management was investigated using hormonal induction to better understand the effect of hormonal treatment of both sexes. Fourteen pairs of pikeperch brood fish were divided into two groups (seven pairs in each group). Seven females in Group A and both sexes in Group B were hormonally injected with 500 IU of hCG per kg. Each pair of brood fish was held separately in a 300-l circular tank with an added spawning material on the bottom. Brood fish were removed from the tanks on the day after spawning; three-hundred randomly selected eggs were removed from the spawning nests and transferred to 250 ml plastic incubators. Sperm samples were collected from males in individual 1-ml syringes. Significant differences in fertilization rate (Group A 59.5%, Group B 80.4%), hatching rate (Group A 51.2%, Group B 71.6%), and number of larvae produced per female (Group A 49 429, Group B 122 000) were observed. Differences were attributable to sperm quality, primarily volume (Group A 0.16 ml, Group B 0.64 ml), and duration of spermatozoa motility (Group A 59.5 s, Group B 97.7 s). Hormone treatment of both sexes is beneficial for pikeperch semi-artificial reproduction by inducing ovulation and improving milt production and spermatozoa quality, fertilization and hatching rate, all contributing to a higher number of produced larvae.